Estimation of Level and Deformed First-Year Sea Ice Surface Roughness in the Canadian Arctic Archipelago from C- and L-Band Synthetic Aperture Radar. Issue 3 (4th July 2019) - Cafarella, Silvie Marie; Scharien, Randall; Geldsetzer, Torsten; Howell, Stephen; Haas, Christian; Segal, Rebecca; Nasonova, Sasha
Abstract: Utilizing synthetic aperture radar (SAR) data to understand and map sea ice roughness is an active area of research. An object-based image analysis is here used to quantitatively link the winter first-year sea ice surface roughness to C-band RADARSAT-2 and L-band ALOS-2 PALSAR-2 SAR backscatter measured in the Canadian Arctic. Results indicate: (1) C-band HH-polarization backscatter is correlated with roughness ( r = 0.86) at a shallow incidence angle; and (2) L-band HH- and VV-polarization backscatter is correlated with roughness ( r = 0.82) at a shallow incidence angle. Retrieval models for surface roughness are developed and applied to the imagery to demonstrate the potential of SAR for mapping deformation with a best case RMSE of 5 mm. Additionally, strong correlations between C- and L-band SAR backscatter acquired during the advanced melt period, and the winter measured surface roughness, are observed. These results are discussed in the context of SAR potentially providing significant sea ice structural information despite the occurrence of melt and presence of surface melt ponds.